Adição de subprodutos da cinza da casca de café (coffea canephora) em massa cerâmica para porcelanato - Dultra, Eduardo Jorge Vidal (2013)
To produce porcelain tiles fluxing agents are used in order to obtain a liquid phase during firing. This liquid phase fills the pores decreasing porosity, water absorption and contributes to material densification. In the porcelain tiles industry, feldspar is the main flux material used, with quantities ranging between 35 and 50%. Studies focus on the discovery of materials with flux characteristics that can reduce the consumption of feldspar by porcelain tiles industry. In this context, the coffee husk ashes, a residue obtained when coffee husks are burned to produce heat for the dryers during the processing of the green fruit, have as main chemical constituents potassium, calcium and magnesium, giving them characteristics of fluxing material. Brazil is the largest coffee producer in the world and is responsible for over 30% of the world s production. In this work a physical treatment of coffee husk ash was carried out in order to eliminate the organic matter and, after this, two by-products were obtained: residual wastes R1 and R2. Both residues were added separately as single fluxes and also in association with feldspar in mixtures with raw materials collected in a porcelain industry located in Dias d Ávila-Ba. The addition of these residues aimed to contribute to the reduction of the consumption of feldspar in the production of porcelain tiles. Specimens were produced with dimensions of 60 mm x 20 mm x 6 mm in an uniaxial die with compacting pressure of 45 MPa. The samples were heated to a temperature of 1200 °C, for 8 minutes. Tests were performed to characterize the raw materials by XRF, XRD, particle size analysis, DTA and TGA and, additionally, the results of the physical properties of water absorption, apparent porosity, linear shrinkage, density, dilatometry, flexural strength and SEM of sintered body were analyzed. Additions of less than 8% of the residue R1 contributed to the decrease of porosity, but the mechanical strength of the samples was not satisfactory. Additions of 5% the R2 residue contributed significantly to decrease the water absorption and apparent porosity, and also to increase the mechanical strength. Samples with addition of feldspar associated with the R2 residue, in proportions of 6.7% of R2 and 6.7% of feldspar, led to results of water absorption of 0.12% and mechanical strength of 46 MPa, having parameters normalized to the manufacture of porcelain stoneware tiles